Decentralized abstractions for multi-agent systems under coupled constraints. (January 2019) - Boskos, Dimitris; Dimarogonas, Dimos V.
Abstract: The goal of this paper is to define abstractions for multi-agent systems with feedback interconnection in their dynamics. In the proposed decentralized framework, we specify a finite or countable transition system for each agent which only takes into account the discrete positions of its neighbors. The dynamics of each agent consist of a feedback component which can guarantee certain system and network requirements and induces the coupled constraints, and additional input terms, which can be exploited for high level planning. In this work, we provide sufficient conditions for space and time discretizations which enable the abstraction of the system's behavior through a discrete transition system. Furthermore, these conditions include design parameters whose tuning provides the possibility for multiple transitions, and hence, the construction of transition systems with motion planning capabilities.